SPE European Formation Damage Conference &Amp; Exhibition 2013
DOI: 10.2118/165175-ms
|View full text |Cite
|
Sign up to set email alerts
|

Novel Water Shutoff Treatments in Gas Wells Using Petroleum External Solutions and Microemulsions

Abstract: The different water shutoff treatments based on in-situ gelation are attractive technologies; however, the field results often fall short of expectation. Reason of unsuccessful treatments might be that the flow resistance against water often develops not in the right time and reservoir space. Therefore, the primary aim of the research project was to develop such chemical systems, which will form the blocking phase triggered by mixing with water. As a novelty, water sensitive petroleum solutions and external mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Calculation of the stress state of the rock in the near-wellbore zone based on geomechanical modeling can make a significant contribution to the optimization of well killing processes. Among the works on the assessment of the stress state in the near-wellbore zone can be distinguished (Elchin et al, 2019;Lakatos et al, 2013;Fischer et al, 1973;Dorman and Udvary, 1996;Bouts et al, 1997;Orlov et al, 1991;Musabirov et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Calculation of the stress state of the rock in the near-wellbore zone based on geomechanical modeling can make a significant contribution to the optimization of well killing processes. Among the works on the assessment of the stress state in the near-wellbore zone can be distinguished (Elchin et al, 2019;Lakatos et al, 2013;Fischer et al, 1973;Dorman and Udvary, 1996;Bouts et al, 1997;Orlov et al, 1991;Musabirov et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Our research was dealt with the examination of emulsions which may occur during enhancement of petroleum exploitation [5,6]. In this process, the aqueous solution and the crude oil mixture get various stable emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results indicated that water permeability dramatically declined, though gas permeability was slightly affected due to polymer adsorption on the pore surface . The traditional water shutoff agents including inorganic substances, polymers, or cross-linking agent–polymers for oil wells are found to impose a great negative impact on gas wells, especially for tight gas formations. Subsequently, a modified polymer–cross-linking process was developed to not only induce gas channels within gel, but also re-establish gas permeability near the wellbore, selectively reducing water permeability . Another sequential gel/gas slug injection process was also proposed to perform water control in gas wells only in medium or high permeable porous media, which can significantly reduce the water–gas ratio .…”
Section: Introductionmentioning
confidence: 99%